Makna dan Nilai Pendidikan pada Kidung Ahsanul Qishos Karya Ahmad Toha serta Pemanfaatannya Sebagai Bahan Pembelajaran Sastra di SMA - Marlina, Lina (Universitas Mathla'ul Anwar Banten, 2023)
This research aims to determine the meaning and educational values of the song Ahsanul Qishos as learning material for literary appreciation in high school. This research uses a qualitative descriptive type or approach with a data collection method using the interview method and a data analysis method using content analysis. The results of the analysis of the 20 hymns have different meanings, including lexical meaning of 8 quotes in several of the hymns analyzed, grammatical meaning of 15 quotes in the analyzed hymns, denotative 20 quotes, connotative 4 quotes, idiom 1 quote, referential 7 quotes, contextual 4 quotes. The educational values found were moral values, social values, religious values and cultural values. The results of this analysis can be used as learning material for literary appreciation in high school, in class X phase E of the independent curriculum, with the aim of learning to analyze the building blocks of a saga. The twenty Ahsanul Qishoh ballads studied can be used as learning material for literature appreciation in the independent curriculum in high school. At the same time, the process of learning the meaning and values of life is based on the educational values inherent in the song. This song is included in the saga in the form of poetry